2013
DOI: 10.1111/trf.12458
|View full text |Cite
|
Sign up to set email alerts
|

Total nucleated cells as a sole predictor of distinct targets of hematopoietic potential (CD34+ cells) in cord blood units: the results of a large series analysis in autologous cord blood units

Abstract: This analysis, carried out on a large, unrestricted CBU series, shows that TNC alone is the best predictor of distinct targets of hematopoietic potential with the chance to predict CBU potentially useful for unrelated recipients or limited for family-directed or autologous use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…62 In Italy, a study of 1309 UCB units collected for autologous UCB banking allowed units to be separated by total nucleated cell count, with larger units potentially being eligible for unrelated use and smaller units for family-directed use. 63 The authors conclude that the integrated bank model would increase public UCBT with a reduction in national health-care system costs as private money is being used to expand public inventory, and the quality of autologous UCB would be improved. Family banking is not available to all as a fee is charged, between US $1350 to $2300 initially at accredited banks and a yearly storage fee of $100 to $175.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…62 In Italy, a study of 1309 UCB units collected for autologous UCB banking allowed units to be separated by total nucleated cell count, with larger units potentially being eligible for unrelated use and smaller units for family-directed use. 63 The authors conclude that the integrated bank model would increase public UCBT with a reduction in national health-care system costs as private money is being used to expand public inventory, and the quality of autologous UCB would be improved. Family banking is not available to all as a fee is charged, between US $1350 to $2300 initially at accredited banks and a yearly storage fee of $100 to $175.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…However, in selected cases, a human leucocyte antigen (HLA) identical sibling UCB can be used for the treatment of a patient in need of transplantation (Gluckman et al , ). One of the main limitations of UCBT is the low cellular content of a single UCB unit (Wagner et al , ; Warkentin, ; Gluckman et al , Barker et al , ; Mazzocchetti et al , ), and the association between cell dose and outcome after UCBT has already been consistently demonstrated (Gluckman et al , ; Barker et al , ; Mazzocchetti et al , ). While public unrelated cord blood banks have set stringent quality criteria (Warkentin, ), UCB units available for related use have often been stored in private facilities or local cell‐therapy units that do not always follow the same rules, especially those concerning the minimum number of total nucleated cells (TNC) collected, as very often they are stored regardless of the cellular content.…”
mentioning
confidence: 99%
“…For autologous CB the safe minimum dose of CD34 + cells is unknown but, due to the lack of histocompatibility diversities, is supposed to be less than that for allogeneic transplantations. Previously, we observed that volume is a less important predictor than TNC for CD34 + cell content and may not be used as a selection criterion [11]. In order to establish a CBU quality, the number of CD34 + and TNC cells in each CBU represent well de ned predictors but also maternal and neonatal factors should be evaluated for a more accurate quality prediction of individual CBU, also considering future perspectives where CBU might be used in autologous or family related settings for new therapeutic indications.…”
mentioning
confidence: 99%